Pemanfaatan Vermikompos Yang Berbeda Terhadap Perubahan Parameter Fisika Pada Media Tanah Gambut - Anggriani, Yuli; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from January to March 2017 in the Kualu Nenas Village, Tambang district, Kampar Regency, Riau and in Environmental Quality Aquaculture, Faculty of Fisheries and Marine University of Riau. The objective of this research is to know the effect of vermicompost type on change of soil physics properties and peat pond water such as the soil color, crude soil fiber, bulk density, soil porosity, temperature, turbidity dan total suspended solid. The experimental design used a complete randomized design (CRD) with four treatments and three replications by linear model of Sudjana (1991). The treatments applied were without vermicompost (P0), vermicompost from human fecal (P1), vermicompost from cow dung (P2), vermicompost from chicken manure (P3). The result of this study showed that P1 (vermicompost from human fecal) was the best treatment for (crude soil fiber 60.3a %; BD 0.41a g/cm3 and porosity 65a %,). For the turbidity and TSS, The best result in P0 (control). For the soil colour of vermicompost is not effect. the temperature was water that range from 26-31oC the range temperature is still quite good for aquatic organism.Keywords : Lumbricus sp., Peat Land, Physical Parameter, Vermicompost